2004
DOI: 10.1590/s0100-67622004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and removal of Michelia champaca L. (Magnoliaceae) in eucalypt stands: the influence of the aril

Abstract: We tested the influence of the aril on seed germination in controlled conditions and on the removal of M. champaca seeds in natural environment. Germination assays were kept at 25 ± 2 °C under continuous white light. Removal experiments were carried out in three "old" (39 to 62-years old) and three "new" (15-years old) eucalypt stands in Horto Florestal Navarro de Andrade, Rio Claro, SP. The results show that the aril inhibits the germination and the seeds exhibit a positively photoblastic reaction. We found h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
2
5
0
1
Order By: Relevance
“…The results in the current study agree with other reports for several other seed-mucilage-bearing species. For example, removing the seed mucilage reportedly favoured the percentage, speed, uniformity of germination, and early development in papaya (Carica papaya [19]), guava (Psidium guajava [20]), citrus [21], red dragon (Hylocereus undatus Haw [22]), passion fruit (Passiflora edulis [23][24][25]), alyssum (Alyssum minus [13]), and lettuce (Lactuca sativa [26]). …”
Section: Discussionmentioning
confidence: 99%
“…The results in the current study agree with other reports for several other seed-mucilage-bearing species. For example, removing the seed mucilage reportedly favoured the percentage, speed, uniformity of germination, and early development in papaya (Carica papaya [19]), guava (Psidium guajava [20]), citrus [21], red dragon (Hylocereus undatus Haw [22]), passion fruit (Passiflora edulis [23][24][25]), alyssum (Alyssum minus [13]), and lettuce (Lactuca sativa [26]). …”
Section: Discussionmentioning
confidence: 99%
“…No correlations were found between this variable and the rest of the values of germination and vigor evaluated. Candiani et al [57] concluded that the germination of Michelia champaca L. seeds is hindered probably due to the presence of inhibiting substances in the aril, is considered as endogenous causes of seed dormancy which include factors such as phytohormones, or by interference with water uptake [58]. Abscisic acid (ABA) is the key inhibitor of germination in Taxus yunnanensis seeds during wet sand storage [59].…”
Section: Resultsmentioning
confidence: 99%
“…Conforme relatos de São-José & Nakagawa (1987) a presença da mucilagem em sementes de maracujá contribuiu para reduzir a porcentagem de germinação. De forma semelhante, Candiani et al (2004) constataram que a presença da mucilagem inibiu a germinação de sementes de champaca e de alface. Ono et al (2004) também observaram problemas na germinação de sementes de mamão, pela presença de substâncias inibidoras na mucilagem.…”
Section: Resultsunclassified